Data Collection, EHRs, and Poverty Determinations. Issue 3 (September 2018) - Konnoth, Craig
Collecting and deploying poverty-related data is an important starting point for leveraging data regarding social determinants of health in precision medicine. However, we must rethink how we collect and deploy such data. Current modes of collection yield imprecise data that is unsuited for research. Better data can be collected by cross-referencing other sources such as employers and public benefit programs, and by incentivizing and encouraging patients and providers to provide more accurate information. Data thus collected can be used to provide appropriate individual-level clinical and non-clinical care, and to systematically determine what share of social resources healthcare should consume.